The Effect of Hedonism and Ease of Use of e-Commerce Feature on Excessive Consumerist Behaviour - Paujiah, Usiah Nurlaela; Achmad, Listian Indriyani; Sakum, Sakum; Mamun, Sukron; Edy, Sarwo (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
The purpose of this study was to determine the effect of hedonism and the ease of use of the Shopee-PayLater feature on consumptive behaviour/excessive consumerist behaviour. Respondents in this study were residents of a housing complex in Bekasi. A sample of 97 people was taken, using the Bernoulli formula. This research used simple descriptive regression analysis and multiple linear regression analysis. The SmartPLS 3.0 application and measurements are used for this purpose. The results of the study indicate that hedonism has a positive and significant effect on excessive consumerist behaviour. The ease of use also has a positive and significant effect on the excessive consumerist behaviour of the community members. People are not really aware of what usury means, so most people do online shopping with a credit system with interest such as shopping now pay later/SPaylater. An understanding of the legal practice of buying and selling in Islam is required. It is the obligation of the scholars to provide more teaching so that the public clearly understands that anything added to the repayment of the loan is forbidden. Islam is a guide for life in this world and in the hereafter